Comparison of cryotherapy session intervals in the treatment of external genital warts - Belkız Uyar; Handan Sacar (Wolters Kluwer Medknow Publications, 2014)
A review of the literature found that the cryotherapy method used to treat external genital warts (EGWs) has been applied with varying intervals between sessions. However, no study has compared the intervals between sessions. The files of 312 patients who were diagnosed with genital warts and underwent cryotherapy were retrospectively reviewed. The patients were divided into two groups: 7-8 days between cryotherapy treatments and 14-21 days between cryotherapy treatments. The number of sessions and recurrence status were recorded for each patient. Cryotherapy methods applied with short intervals, such as 7-8 days, are more effective, requiring fewer sessions and less time when compared with longer intervals (p < 0.0001).